Microwave‐Assisted Synthesis of NiMn2O4 Grown on Nickel Foam as Electrode Material for High‐Performance Supercapacitors. Issue 22 (14th June 2021) - Du, Xiaomei; Yang, Liu; Fu, Yingqing; Liu, Sen; Huang, Naibao; Wang, Shusen
Abstract: The spinel NiMn2 O4 has been directly grown on 3D nickel foam by combining a simple microwave‐assisted hydrothermal with annealing process at different temperatures (350 °C to 650 °C), which can be used as a binder‐free electrode for high‐performance supercapacitors. The results indicate that the pure NiMn2 O4 can be obtained below 550 °C. The as‐prepared NiMn2 O4 at 450 °C has the largest specific capacitance of 802 F g −1 at 1 A g −1 and excellent cycle stability (61 % capacity retention after 5000 cycles at 10 A g −1 ) among all the obtained samples. This outstanding electrochemical performance may be attributed to its relatively large grain size, high specific surface area, and appropriate pore structure. This indicates that NiMn2 O4 grown on nickel foam shows great potential as an electrode material for supercapacitors. Abstract : The microwave‐assisted hydrothermally synthesized samples were annealed at different temperatures (350 °C, 450 °C, 550 °C, and 650 °C, respectively). When the selected annealing temperature is 450 °C, the spinel NiMn2 O4 grown in situ on the 3D nickel foam can be obtained, and it has the best electrochemical performance as a binder‐free electrode for supercapacitors.